Epinephelus adscensionis - Heemstra, P. C. (Zenodo, 1991)
Epinephelus adscensionis (OSBECK, 1765) Fig. 4. d Perca tota maculis . SEBA, 1758; 76, Pl. 27, Fig. 7 (type locality, unknown). Trachinus adscensionis OSEECK, 1765: 388 (type locality, Ascension Island, South Atlantic Ocean; holotype not located). Perca stellio WALBAUM, 1792: 349 (based on Perca tota maculis of SEBA). Trachinus osbeck LACEPÈDE, 1800: 364 (substitute for Trachinus adscensionis OSBECK; type locality, Ascension Island). Serranus pixanga VALENCIENNES, in Cuv. & VAL., 1828: 383 (type locality unknown [presumably Brazil]; based on a description by MARCGRAVE). Serranus nigriceps VALENCIENNES, m Cuv. & VAL., 1830: 517 (type locality unknown, holotype MNHN 7393 (264 mm.). Serranus impetiginosus MÜLLER & TROSCHEL, 1848: 665 (type locality, Barbados; holotype not located). Serranas capreolus POEY, 1860: 145 (type locality, Cuba; holotype not located). Serranus varius BOCOURT, 1868: 222 (type locality, Gulf of Mexico; holotype MNHN 5190 (166 mm)- Epinephelus adscensionis : See C. L. SMITH (1971: 145) for numerous additional references. Diagnosis : Dorsal fin XL, 16- 18; anal fin III,8; pectoral fin rays 18 -20; lateral-line scales 48-53; lateral scale series 92- 108; gill-rakers 7-9 + 16- 19 including 2-7 rudiments on each limb. Body depth less than head length, contained 2.6-3.2 times in SL (for fish 13 -38 cm. SL); head length 2.1 - 2.5 times in SL; pectoral fins longer than pelvics, 1.5 -2.1 times in head length; pelvic fins 1.8 -2.3 times in head length for fish 10- 19 cm. SL, 2.2-2.7 times in head length for fish 20-38 cm. SL. Rear margin of caudal fin convex; dorsal fin with the fourth or fifth spine longest and the interspinous membranes distinctly incised. Interorbital area flat or slightly concave; preopercle evenly serrate, without salient angle; subopercle and interopercle smooth; nostrils subequal. Lateral body scales distinctly ctenoid, with auxiliary scales. Colour : Head, body and fins generally buff or pale greenish, covered with reddish brown spots (spots fewer but larger on ...